The Importance of Early Physical Therapy in Tibial Plateau Fracture: A Case Report - Marchioni, Victoria; Veiga Quemelo, Paulo Roberto (International Journal of Orthopedics and Rehabilitation, 2019)
Introduction: Tibial plateau fractures are complex condition that affect functional knee movement. The case report would draw attention to the importance of early physical therapy in these cases. Case report: A 33-year-old Brazilian man, had a motorcycle accident that resulted in a right tibial plateau fracture. After three months post-op of osteosynthesis patient came to start the rehabilitation process. Results: During the physical therapy evaluation, we observed an important capsular restriction with reduction of the motion range (just 15º right knee flexion), and muscular hypotrophy of right lower limb. Late rehabilitation process included: active and passive mobilization of knee; progressive discharge of weight in right lower limb; progressive muscle strengthening of the right lower limb and proprioceptive training. After three months of rehabilitation, we observed little improvement in knee range of motion (35º right knee flexion), and improvement of muscle strength and gait. Conclusion: In Brazil, motorcycle accidents that result in the fracture of the lower limb are frequent. In this report, the difficulties and complications of the late rehabilitation process were observed. This case report seeks to draw attention to the future inclusion of physical therapy in hospital routines, along with the referral of patients to early clinical rehabilitation process with the objective of obtaining optimal recovery of these patients.